Evaluación del sistema productivo con relación a la eficiencia y productividad en la planta criogénica ASU de la empresa INDURA ECUADOR S.A. 2015. Elaboración del plan de mejoras para la operación y control del sistema de gestión integral. - Andrango Guayasamín, Raúl Heriberto (2015)
The present study has as purpose the evaluation of the productivity system in the ASU plant of the company Indura Ecuador, to improve its efficiency and productivity through the recovery of the residual oxygen. The research analyzed the system of production and the productive efficiency through the lifting of information in the operation process and current production, to subsequently make a proposal for improvement. The proposed study is presented as a non-experimental research and takes a form of field, applying tools such as observation and documentary review to evaluate the productive system of the ASU plant. The obtained results allowed identifying operational problems at every stage of the process as well as low productivity due to the lack of updated instructional for the control and monitoring of plant operations. Then a proposal was raised by developing improvement plan for the operation and control. This work allowed us to analyze some case studies and options to improve the productivity and profitability of the residual oxygen recovered. It is concluded that the plant has peculiarities in the operation, control and monitoring, where operators play an important role to obtain an adequate efficiency through the use of instructional work. The introduction of new technologies and proven updates, allow you to reduce operating costs or improve the plant's capacity in ways that enhance their statistics.